2013
DOI: 10.4172/2155-6156.1000250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gestational Diabetes on Circulating Levels of Maternal and Neonatal Carnitine

Abstract: Objectives: Free carnitine is reported to decrease in normal pregnancies whereas data on the effect of gestational diabetes mellitus (GDM) on maternal and offspring carnitine status are lacking. This study aimed to assess changes in carnitine status in mothers with GDM and the offspring. Subjects/methods:Prospective case-control study of 54 pairs of mothers -neonates (27 with GDM and 27 with normal pregnancies) and 26 non-pregnant controls. Serum glucose, lipids, and total fatty acids, blood β-hydroxybutyric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…According to our study the results showed that GDM was associated with increased cholesterol Figure 1. This is what was previously confirmed 35 .…”
Section: Discussionsupporting
confidence: 92%
“…According to our study the results showed that GDM was associated with increased cholesterol Figure 1. This is what was previously confirmed 35 .…”
Section: Discussionsupporting
confidence: 92%
“…Another prospective study did not observe significant association of total acylcarnitine concentrations with GDM risk. However, association of individual acylcarnitine species with GDM were not disentangled in this study [16]. Taken together, it calls for longitudinal investigation of individual acylcarnitine species throughout pregnancy to advance our understanding of their potentially distinct pathophysiologic roles in the development of GDM.…”
Section: Introductionmentioning
confidence: 70%
“…Although findings from several emerging studies were promising, inferences were hindered by cross-sectional design and small sample sizes [12e14]. We are aware of only two prospective studies to date [15,16]. One study associated three short-chain carnitine esters, C2, C4 and IsoC4, with the risk of GDM prospectively; however, only a few selected esters were measured in this study [15].…”
Section: Introductionmentioning
confidence: 92%
“…However, the majority of individual NEFAs was not significantly different between the GDM cases and controls. It was concluded that the differences in the maternal plasma NEAF composition between the GDM cases and the healthy controls were very subtle 37 , and our analysis had reached a limit of untargeted GC-MS analysis with the selected data normalisation methods. By using targeted GC-MS analysis, Chen, et al ., reported that the concentrations of NEFAs in maternal serum had a “graded” (or incremental) relationship with the severity of maternal hyperglycaemia 38 .…”
Section: Resultsmentioning
confidence: 99%